A comparative study of Danticat’s The Farming of Bones and Morrison’s Beloved - Vega-gonzález, Susana (Estudios Ingleses de la Universidad Complutense, 2005)
The aim of this paper is to analyse the main thematic and structural lines from which Edwidge Danticat’s The Farming of Bones and Toni Morrison’s Beloved can be compared. In their acclaimed novels, Danticat and Morrison engage in a revision and rewriting of history, taking as the basis of their narratives two historical episodes which appear marked by violence and racial oppression. Since issues of power and interpretation in the creation of history often render silenced and manipulated histories of marginalized ethnic groups, Danticat and Morrison take it upon themselves to fill historical gaps concerning African American slaves and Haitian American cane workers. Both authors undertake their historical revisions through a similar narrative technique, which includes the use of biblical passages, dreams, memory, storytelling and metaphor. Such elements are disclosed as apt means to create a counter-history where previously silenced voices can be heard.